Low-value care and endoscopy in dyspepsia: A retrospective observational study from a metropolitan Australian hospital. (2020) - Lin, Lei; Khaing, Myat Myat; Ea, Vinny; Kellar, Petrina; Hartnell, Felicity; Croese, John; Hodgson, Ruth; James, Thomas; Franz, Robert; Hughes, Andrew; Iswariah, Harish; Shaw, Ian; et al.
No abstract available